MORPHOLOGICAL VARIATIONS OF CULTURED AND WILD Oreochromis niloticus FROM IBADAN AND KAINJI IN NIGERIAB - OLUFEAGBA, S. O; ALADELE, S. E; OKOMODA, V. T; OKERE, A.U; ODUOYE, O. T; HASSAN , T. (Nigerian Journal of Fisheries, 2015)
This study investigated the morphological variations of wild and cultured Oreochromis niloticus from Kainji and Ibadan in Nigeria; wild fishes were collected from various landing sites of the Lake Kainji and Asejire, Ibadan. Cultured fish were collected from fish farms with known breeding history in the two environment, samples were stored under ice and transported to the laboratory for morphological characterization. Results obtained reveals significant higher values in most morphometric parameters of the cultured specimen from the different environments compared to their wild counterparts, however condition factor of the fish were higher for fishes in the wild (4.41 and 4.16 for Ibadan and Kainji respectively) compared to those in the cultured environment (2.94 and 3.44 for Ibadan and Kainji respectively). Discriminate analysis showed clear overlap of meristic data for the different environments; however in morphometric parameters, fish from the Lake Kainji slightly overlap with its culture counterpart from the same environment but clearly separate itself from those from Ibadan.